On the cranial morphology of Elapomorphus, Phalotris and Apostolepis (Serpentes: Colubridae), and its phylogenetic significance - Hofstadler-Deiques, Clarice; de Lema, Thales (Zootaxa, 2005)
The skull of Elapomorphus quinquelineatus is described in detail and the phylogenetic relationships among the neotropical snakes Apostolepis, Elapomorphus and Phalotris are studied based on 17 skull characters and 3 external morphological characters. Representants of the subfamily Xenodontinae were included in this work for phylogenetic comparisons. The results indicate elapomorphine snakes form a clade supported by 3 synapomorphies, which, in turn, is closely related to representatives of the African Atractaspididae, this latter assemblage being supported by 9 synapomorphies. The revalidation of the name Elapomorphinae Jan 1862, as subfamily of the Colubridae is proposed.